PENGGUNAAN MODEL PROBLEM BASED INSTRUCTION UNTUK MENINGKATKAN CIVIC SKILL PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN - Yanzi, Hermi (Jurnal Pendidikan Progresif, 2016)
The Use of Problem Based Instruction Model to Increase Civic Skill in Civic Education Learning. The aim of this research was to analyze and to describe the implementation of Problem Based Instruction Model to increase students’ civic skill at SMPN 3 Tegineneng, Academic Year 2014/2015. The research used Classroom Action Research. Based on the research, it was known that PKn learning by implementing PBI Model for students through Classroom Action Research gives students motivation during learning proccess, guides students entirely, students are looked active during the learning process, provides more time to interact with students, and gives feedback as soon as possible which is proved that it can increase the students’ learning activity. It can conclude that students’ civic skill has increased il line with the research success target that had been decided. With the data acquisition in cycle I is 52,73%, increase in cyle II which is 70,31% and 81,22% in cycle III. Keywords: civic skill, PBI, civic education